The Impact of Severe Mental Illness (SMI) on Oral Health-Related Quality of Life (OHRQoL): A Mixed-Methods Study in Surabaya, Indonesia - Syaifudin Syaifudin; Duru Carissa Neuer; Muhammad Ashraf; Aprilia Sari (HM Publisher, 2025)
Introduction: Severe Mental Illness (SMI) often leads to neglect of personal care, including oral hygiene, and may be associated with specific oral health challenges. This study aimed to comprehensively assess the impact of SMI on Oral Health-Related Quality of Life (OHRQoL) in a population in Surabaya, Indonesia. Methods: A cross-sectional study was conducted involving 120 participants with SMI (schizophrenia, bipolar disorder, and major depressive disorder with psychotic features) recruited from a tertiary psychiatric hospital and community mental health centers in Surabaya, and 120 age- and sex-matched controls without SMI. OHRQoL was assessed quantitatively using the Indonesian version of the Oral Health Impact Profile-14 (OHIP-14). Semi-structured interviews were conducted with a subset of 30 participants with SMI to explore their experiences and perceptions regarding oral health. Oral examinations were performed on all participants to assess Decayed, Missing, and Filled Teeth (DMFT) index, Community Periodontal Index (CPI), and presence of oral mucosal lesions. Results: Participants with SMI had significantly higher mean OHIP-14 scores (32.5 ± 8.2) compared to controls (14.1 ± 4.5) (p < 0.001), indicating poorer OHRQoL. The DMFT index was also significantly higher in the SMI group (12.8 ± 3.7) compared to controls (6.2 ± 2.1) (p < 0.001), and CPI scores indicated worse periodontal health in the SMI group. Qualitative analysis revealed key themes: barriers to accessing dental care (financial constraints, fear, lack of transportation), challenges with daily oral hygiene practices (forgetfulness, lack of motivation, side effects of medication), and limited awareness of the importance of oral health. Conclusion: Individuals with SMI in Surabaya, Indonesia, experience significantly poorer OHRQoL compared to the general population. This is associated with poorer objective oral health status and multiple, interlinked barriers to care. Integrated mental health and oral health services, tailored interventions to improve oral hygiene practices, and increased awareness campaigns are crucial to address this disparity.